2018
DOI: 10.2135/cropsci2017.10.0608
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis of Fusarium Root Rot Resistance in an Andean × Middle American Common Bean RIL Population

Abstract: Fusarium root rot (FRR) is a soil‐borne disease that constrains common bean (Phaseolus vulgaris L.) production. Its causal pathogens include clade 2 members of the Fusarium solani (Mart.) Sacc. species complex. Here, we characterize common bean reaction to different Fusarium species and identify genomic regions associated with resistance. Four Fusarium species—F. brasiliense T. Aoki & O'Donnell, F. cuneirostrum O'Donnell & T. Aoki, F. solani sensu stricto, and F. oxysporum Schltdl. sensu lato—were tested for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…In a previous study, FRR was determined to be controlled by root genotype and root vigor played an important part in resistance (Cichy et al, 2007). Wang et al (2018) demonstrated that resistant lines had a slightly higher root biomass and hypothesized that some of the QTL associated with FRR resistance are more likely related to root biomass. High resistance consistently associated with root architecture, which indicates that these may be dependent traits and need to be considered when selecting lines for resistance breeding (Strock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, FRR was determined to be controlled by root genotype and root vigor played an important part in resistance (Cichy et al, 2007). Wang et al (2018) demonstrated that resistant lines had a slightly higher root biomass and hypothesized that some of the QTL associated with FRR resistance are more likely related to root biomass. High resistance consistently associated with root architecture, which indicates that these may be dependent traits and need to be considered when selecting lines for resistance breeding (Strock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a second bean study, one QTL was identified for FRR explaining just 10% of the variance (LOD 3.2) [ 47 ]. Conversely, in a recent bean study, QTLs for F. solani resistance identified 17 QTL related to FRR explaining at most 16% of the variance (LOD 5.84) [ 48 ]. In the closely related legume, lentil, Fusarium root rot was identified as a problem by Hwang et al [ 49 ] and noted as an increasing production constraint [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have mapped several traits associated with FRR on chromosomes Pv02, Pv03, Pv05, Pv07 and Pv11 using SSR and SNP markers (Hagerty et al, 2015; Kamfwa et al, 2013; Nakedde et al, 2016; Wang et al, 2018). In another study, Soltani et al (2018) reported high susceptibility of Andean genotypes to Pythium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The second region was 162.39 Kb flanked by markers SNP ss715645960 (44.95 Mb) and ss715645959 (44.79 Mb) in LD ( r 2 > .61; D ′ > 0.72). Wang et al (2018) reported QTL for FRR resistance and control root dry weight on Pv02 in the CAL96 × MLB‐49‐89A RIL population. The QTL FRR2.2 CM at 35.40 Mb and FRR2.3 CM at 30.57 Mb for FRR disease severity in the greenhouse and field colocalized with RTWC2.1 CM at 32.62 Mb for control root dry weight and STWC2.1 CM at 46.31 Mb for control shoot dry weight, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation